Outras verdades, muito extraordinárias, do grande sertão - Sousa, Maria do Perpetuo Socorro Guterres de (2010)
This study explores the symbolism of evil way in the novel Grande sertão: veredas, by Guimarães Rosa, regarding faustian pact by Goethe, and so tries to understand how the rosiana language are present to the strategies which put in suspense the effectiveness of the demonic agreement and enable, with poetic intensity, different interpretations, especially as regards the anguish of the human condition. This research thus has drawn upon the Mythical Symbolism, in Literary Criticism and aspects of Metaphysics, in addition to analyzing classic literary essays in approaching of Rosa s masterpiece structure. It has also demonstrated that the incorporation of the Faust legend in Grande sertão reflects the same desire for happiness that is not done completely, and in this manner, instigates a discussion about the limits to the satisfaction of being human. Therefore, it has observed that epic narrative of ex-gangster Riobaldo to the doctor of city speculates on human man, in the continuous learning of his passing